Analisis Redesain Pondasi Pada Pembangunan Proyek Universitas Pembangunan Nasional Veteran Surabaya - Muhamad Fadlan Alhamid (JURNAL ILMIAH NUSANTARA, 2025)
Twin Tower Building of UPN East Java is used for lectures. This building has an area of ​​25936.5 m2 which will later be used by faculties at UPN East Java as a place of lectures. During the construction stage, several problems were found in the field during the PDA (Pile Driving Analyzer) test. The results of the PDA test showed that the bearing capacity of the foundation had not met the planned bearing capacity, so reinforcement was carried out on the foundation by adding the number of pile points and making the foundation a pile group foundation system. The purpose of this study was to analyze the comparison of the number of foundation piles, pilecap reinforcement, costs, and implementation time between piles and boredpile piles. From the results of the study, the number of spun piles was 389 and the boredpile foundation was 258. Spun pile cost is Rp 45,903,011,000 while the foundation using BorePile is Rp 64,156,212,000. Implementation time of Spun Pile and pile cap reinforcement in the initial design obtained an estimated day of 108 working days, while the implementation time of the Borepile foundation requires a longer estimated time of 180 working days.